MANAGEMENT OF THE HIGHER EDUCATION INSTITUTIONS INNOVATIVE POTENTIAL: FORMALIZATION AND EVALUATION - Braslavska, Oksana; Penkova, Oksana; Plets, Ivan; Sus, Taras; Biloshkurska, Nataliia; Biloshkurskyi, Mykola (Revista Inclusiones, 2020)
The purpose of this paper is to improve the innovation management of higher education institutions, taking into account the peculiarities of formalizing the structure of innovation potential, ranking, and statistical evaluation. It was used the following methods: comparative analysis, induction and deduction, sum of places method, graphic expression of statistical data, correlation analysis, linear multifactorial regression analysis, and others. The authors proposed to solve the problem of formalization of innovative potential through the systematization of 16 indicators into 4 components: physical capital potential, human capital potential, potential of government regulation, and higher education services market potential. The innovation potential management ranking was developed and tested according to the data of 20 Ukrainian pedagogical higher education institutions, using the sum of places method. It is proved the inverse relationship between the number of enrolled students and the higher education institutions sums of places. For the first time, a statistical multicollinearity test was developed and implemented as part of the correlation analysis. Statistical evaluation of the impact of innovation potential on the higher education institutions development has been improved using linear multivariate regression analysis. This evaluation shows that the most significant is the higher education services market potential.